ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KETIMPANGAN WILAYAH DI PROPINSI SULAWESI SELATAN TAHUN 2010-2016 - Yusniar, Retty (Universitas Halu Oleo, 2020)
This study aims to analyze how much influence regional income, labour force and human development index have on regional inequality in South Sulawesi Province during 2010-2016. The province of South Sulawesi was choosen because based on the data from the provincial statistics center, it showed significant economic growth in 2016. The data used in this study used data from the statistical center of South Sulawesi Province. The data analysis method used in this study is Index Williamson method. The results of this study indicate that the Labor Force variable shows a positive and significant influence on regional inequality. Regional income variables have a negative but significant effect on regional inequality, while the human development index variable has no effect on regional inequality in South Sulawesi.